Low-alkali-high temperature reduction of RNA of microbial biomass protein fermented from coconut (Cocos nucifera Linn.) residue - Santos Maria Janet Venson; De Leon, Sonia Y. (1993.)
Using low-alkali-high-temperature treatment, this study aimed to reduce the ribonucleic acid content of Microbial Biomass Protein (MBP) fermented from coconut (Cocos nucifera Linn.) residue as produced by Dumelod (1993). The MBP analyte was incubated with 0.025 N NaOH at pH 10-10.5 and 80°C for four hours. Such treatment successfully reduced RNA from 11.40% to negligible amounts; however, these figures are estimates due to limitations inherent in the methodology. Resultant changes in protein levels were also measured. Average initial true protein value was 27.22%. After LAHT treatment, the true protein was reduced to 23.91%. It is suggested that studies be conducted for determining the nature of proteins present in the MBP analyte to establish the appropriate procedures for the assay. Furthermore, experiments using other quantitative methods should be conducted to exactly determine the cause of reduction of true protein values after extraction of RNA.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Coconut; Single cell protein